2016
DOI: 10.1007/s12011-016-0671-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Zinc and Magnesium against Cadmium Nephrotoxicity in Male Wistar Rats

Abstract: Cd is a toxic metal that has a destructive impact on most organ systems. This work aims to determine Zn or Mg protective effects against Cd renal toxicity. In this study, rats were divided into six groups. The Cd group was treated with 1 mg Cd/kg, and the control group received 0.5 cm normal saline, intraperitoneally. The other four groups received one of the following dosages of 1 mg/kg Cd + 0.5 mg/kg Zn, 1 mg/kg Cd + 1.5 mg/kg Zn, 1 mg/kg Cd + 0.5 mg/kg Mg, or 1 mg/kg Cd + 1.5 mg/kg Mg through IP injection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…It is well established that the toxicity of cadmium promotes an imbalance in antioxidant defense system, reducing the endogenous antioxidant enzymatic activity, such as superoxide dismutase and catalase [40]. Our results showed that cadmium impairs the gene expression of CuZn-SOD and catalase.…”
Section: Discussionsupporting
confidence: 54%
“…It is well established that the toxicity of cadmium promotes an imbalance in antioxidant defense system, reducing the endogenous antioxidant enzymatic activity, such as superoxide dismutase and catalase [40]. Our results showed that cadmium impairs the gene expression of CuZn-SOD and catalase.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, it has been suggested that long-term exposure to Cd exacerbates the CKD-related decline in GFR [179,180,181,182]. Moreover, exposure to Cd or other nephrotoxicants may further reduce or completely eliminate the renal functional reserve and the ability of the remaining functional renal mass to maintain normal homeostasis when challenged [12,183,184,185]. Indeed, Sprague-Dawley rats exposed chronically to oral Cd have been shown to have less renal functional reserve than unexposed rats [12].…”
Section: Environmentally Relevant Toxic Metalsmentioning
confidence: 99%
“…In fact, a tendency toward the decrease in the weight of the kidneys was observed, especially in males. This alteration has been related to nephrotoxicity, such as necrosis and degenerative damage (Babaknejad, Moshtaghie, Nayeri, Hani, & Bahrami, ), which was confirmed by histopathological and biochemical findings, as described below.…”
Section: Resultsmentioning
confidence: 60%